Question and Answers Forum

All Questions      Topic List

Others Questions

Previous in All Question      Next in All Question      

Previous in Others      Next in Others      

Question Number 76724 by Rio Michael last updated on 29/Dec/19

∫_0 ^3 ∣x^2 −1∣ dx ≡

$$\int_{\mathrm{0}} ^{\mathrm{3}} \mid\mathrm{x}^{\mathrm{2}} −\mathrm{1}\mid\:\mathrm{dx}\:\equiv\: \\ $$

Commented by abdomathmax last updated on 30/Dec/19

∫_0 ^3 ∣x^2 −1∣dx =∫_0 ^1 (1−x^2 )dx +∫_1 ^3 (x^2 −1)dx  =[x−(x^3 /3)]_0 ^1 +[(x^3 /3)−x]_1 ^3 =1−(1/3) +(3^2 −3)−((1/3)−1)  =(2/3) +6+(2/3) =(4/3)+6 =((22)/3)

$$\int_{\mathrm{0}} ^{\mathrm{3}} \mid{x}^{\mathrm{2}} −\mathrm{1}\mid{dx}\:=\int_{\mathrm{0}} ^{\mathrm{1}} \left(\mathrm{1}−{x}^{\mathrm{2}} \right){dx}\:+\int_{\mathrm{1}} ^{\mathrm{3}} \left({x}^{\mathrm{2}} −\mathrm{1}\right){dx} \\ $$$$=\left[{x}−\frac{{x}^{\mathrm{3}} }{\mathrm{3}}\right]_{\mathrm{0}} ^{\mathrm{1}} +\left[\frac{{x}^{\mathrm{3}} }{\mathrm{3}}−{x}\right]_{\mathrm{1}} ^{\mathrm{3}} =\mathrm{1}−\frac{\mathrm{1}}{\mathrm{3}}\:+\left(\mathrm{3}^{\mathrm{2}} −\mathrm{3}\right)−\left(\frac{\mathrm{1}}{\mathrm{3}}−\mathrm{1}\right) \\ $$$$=\frac{\mathrm{2}}{\mathrm{3}}\:+\mathrm{6}+\frac{\mathrm{2}}{\mathrm{3}}\:=\frac{\mathrm{4}}{\mathrm{3}}+\mathrm{6}\:=\frac{\mathrm{22}}{\mathrm{3}} \\ $$$$ \\ $$

Answered by MJS last updated on 30/Dec/19

x^2 −1=0 ⇒ x=±1  0≤x<1: x^2 −1<0 ⇒ ∣x^2 −1∣=1−x^2   1≤x≤3: x^2 −1≥0 ⇒ ∣x^2 −1∣=x^2 −1  ∫_0 ^3 ∣x^2 −1∣dx=∫_0 ^1 (1−x^2 )dx+∫_1 ^3 (x^2 −1)dx=  =[x−(x^3 /3)]_0 ^1 +[(x^3 /3)−x]_1 ^3 =((2/3)−0)+(6+(2/3))=((22)/3)

$${x}^{\mathrm{2}} −\mathrm{1}=\mathrm{0}\:\Rightarrow\:{x}=\pm\mathrm{1} \\ $$$$\mathrm{0}\leqslant{x}<\mathrm{1}:\:{x}^{\mathrm{2}} −\mathrm{1}<\mathrm{0}\:\Rightarrow\:\mid{x}^{\mathrm{2}} −\mathrm{1}\mid=\mathrm{1}−{x}^{\mathrm{2}} \\ $$$$\mathrm{1}\leqslant{x}\leqslant\mathrm{3}:\:{x}^{\mathrm{2}} −\mathrm{1}\geqslant\mathrm{0}\:\Rightarrow\:\mid{x}^{\mathrm{2}} −\mathrm{1}\mid={x}^{\mathrm{2}} −\mathrm{1} \\ $$$$\underset{\mathrm{0}} {\overset{\mathrm{3}} {\int}}\mid{x}^{\mathrm{2}} −\mathrm{1}\mid{dx}=\underset{\mathrm{0}} {\overset{\mathrm{1}} {\int}}\left(\mathrm{1}−{x}^{\mathrm{2}} \right){dx}+\underset{\mathrm{1}} {\overset{\mathrm{3}} {\int}}\left({x}^{\mathrm{2}} −\mathrm{1}\right){dx}= \\ $$$$=\left[{x}−\frac{{x}^{\mathrm{3}} }{\mathrm{3}}\right]_{\mathrm{0}} ^{\mathrm{1}} +\left[\frac{{x}^{\mathrm{3}} }{\mathrm{3}}−{x}\right]_{\mathrm{1}} ^{\mathrm{3}} =\left(\frac{\mathrm{2}}{\mathrm{3}}−\mathrm{0}\right)+\left(\mathrm{6}+\frac{\mathrm{2}}{\mathrm{3}}\right)=\frac{\mathrm{22}}{\mathrm{3}} \\ $$

Commented by Rio Michael last updated on 30/Dec/19

thanks

$$\mathrm{thanks} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com